Local Wisdom Based Procedure Text Materials for Grade VII Students at SMP Negeri 12 Magelang - Alhafidz, Zidan; Alhumairo, Devi Iqlima; Lestari, Siti Anggita Puji; Widyaningsih, Arum Cahya; Sari, Halim Bi Nuri Syamsika (SAKAGURU: Journal of Pedagogy and Creative Teacher, 2025)
Abstract Indonesian language learning at the junior high school level should ideally not only focus on linguistic aspects, but also be a means to instil local cultural values that are relevant to the lives of students. Unfortunately, Indonesian textbooks provided by the Ministry of Education and Culture have not fully accommodated the local content, especially in learning procedure texts. Based on observations and interviews conducted at SMP Negeri 12 Magelang, it was found that teachers and learners need teaching materials for procedure texts that are integrated with local wisdom. This study aims to: (1) describe the need for developing teaching materials based on local wisdom; (2) explain the stages of developing teaching materials; and (3) evaluate the feasibility of the products developed. This research uses the Research and Development (R&D) method of the Borg and Gall model, but only up to the product validation stage. Data collection techniques include observation, interviews, and distributing questionnaires to respondents, and analysed descriptively. The results of validation by media experts obtained a score of 96.25%, linguists 85.00%, and material experts 75.00%. Based on these results, teaching materials for procedure texts based on local wisdom are declared very feasible to use in learning Indonesian language in grade VII SMP.